Sins of the fathers eaudiobook - Jance, J. A. (J. P. Beaumont, 2019)
Seattle investigator J. P. Beaumont is drawn into an intriguing, and shockingly personal, case in this superb tale of suspense from New York Times bestselling author J. A. Jance. Former Seattle homicide cop, J. P. Beaumont, is learning to enjoy the new realities of retirement—doing morning crossword puzzles by a roaring fireplace; playing frisbee with his new dog; having quiet lunches with his still working wife. But then his past comes calling.   When a long ago acquaintance, Alan Dale, shows up on Beau's doorstep with a newborn infant in hand and asking for help locating his missing daughter, Beau finds himself faced with an investigation that will turn his own life upside down by dragging his none-too-stellar past onto a roller-coaster ride that may well derail his serene present. It turns out that, even in retirement. murder is still the name of J. P. Beaumont's game.